"POETIC PARALLELS: AN ANALYSIS OF THE WORK OF ERKIN VAKHIDOV AND SERGEI YESENIN" - Kodirova Ozoda is a teacher of the Department of Methodology of the Russian language, Ferghana State University, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
The article analyzes the work of Uzbek poet Erkin Vakhidov and Russian poet Sergei Yesenin, revealing parallels in their poetic themes and style. Charming poets turn to the themes of love, adoration and philosophy, chilling lyricism and a philosophical approach to life. The images and motifs used by the poets are analyzed, and patterns at the junction of human life and existence are revealed. Keywords: a mixture of life, poetry, poet, novel, philosophical subtext, comparative analysis of creations, lifestyle